Kepercayan dan Persepsi Kemudahan Penggunaan terhadap Keputusan Pembelian Mengunakan Pinjaman Online Shopee Paylater di Kota Semarang - Nur Fadilah Zuniar; Euis Soliha (Journal of Management and Bussines (JOMB), 2024)
This research aims to explore the influence of competence and professionalism on audit quality, by considering the role of auditor ethics as a mediating variable. The research method applied is a quantitative method, and data analysis is carried out using Partial Least Square (PLS). The results of this research show that auditor competence and professionalism have a positive and significant impact on audit quality, both directly and through auditor ethics as a mediator. These findings provide an important contribution in understanding the complex relationship between individual auditor characteristics, aspects of professionalism, and ethical integrity in the audit context. The conclusion is that the implications of the results of this research can provide deeper insight for practitioners, regulators and researchers in developing more effective and quality audit practices. Keywords: Trust, Purchase Decision, Online Loans, Shopee PayLater